Korelasi Antara Pengetahuan dan Tindakan Pencarian Perawatan Gangguan Menstruasi pada Remaja Putri di Kabupaten Semarang: Correlation between Knowledge and Actions to Seek Treatment for Menstrual Disorders among Adolescent Girls in Semarang Regency - Dewi Elliana; Dewi Puspitaningrum (Universitas Ngudi waluyo, 2025)
Menstruation is a physiological process experienced by adolescent girls, but common menstrual disorders often occur in adolescence, menstrual disorders such as dysmenorrhea and irregular cycles are common. These disorders can interfere with daily activities and quality of life. In Semarang Regency, the average age of menarche was reported to be 11.4 years. These menstrual disorders are often ignored, resulting in negative impacts on health. This study aimed to analyze the relationship between knowledge level and treatment-seeking actions for menstrual disorders among adolescent girls in Semarang Regency. This study used a cross-sectional design with an analytic observational approach. This study used a cross-sectional design with an analytic observational approach. A sample of 30 adolescent girls in Semarang Regency was selected using a total sampling technique, which met the criteria of already having menstruation and experiencing menstrual disorders. Data collection used a closed questionnaire that measured the level of knowledge (good/lack) and the type of care-seeking action (independent non-medical/medical self). Data were analyzed univariately for frequency distribution and bivariately using the Chi-Square test with a significance level of α=0.05. The results showed 77% of respondents had good knowledge and 67% performed non-medical self-care. There was a significant relationship between knowledge level and care-seeking behavior (p=0.011). Conclusion: Adolescents with good knowledge tend to choose more appropriate treatment actions.Reproductive health education, especially in better care-seeking behavior among adolescent girls, needs to be improved through school and family approaches. Abstrak Menstruasi merupakan proses fisiologis yang dialami remaja putri, namun gangguan menstruasi yang umum terjadi seringkali pada usia remaja, gangguan menstruasi seperti dismenore dan siklus tidak teratur banyak terjadi. Gangguan ini dapat mengganggu aktivitas sehari-hari dan kualitas hidup. Di Kabupaten Semarang, usia rata-rata menarche dilaporkan 11,4 tahun. Gangguan menstruasi ini seringkali diabaikan sehingga berdampak negatif pada kesehatan. Penelitian ini bertujuan menganalisis hubungan antara tingkat pengetahuan dan tindakan pencarian perawatan gangguan menstruasi pada remaja putri di Kabupaten Semarang. Penelitian ini menggunakan desain cross-sectional dengan pendekatan observasional analitik. Sampel sebanyak 30 remaja putri di Kabupaten Semarang dipilih dengan teknik total sampling, yang memenuhi kriteria sudah mengalami menstruasi dan mengalami gangguan menstruasi.Pengumpulan data menggunakan kuesioner tertutup yang mengukur tingkat pengetahuan (baik/kurang) dan jenis tindakan pencarian perawatan (mandiri nonmedis/mandiri medis). Data dianalisis secara univariat untuk distribusi frekuensi dan bivariat menggunakan uji Chi-Square dengan tingkat signifikansi α=0,05. Hasil penelitian menunjukkan 77% responden memiliki pengetahuan baik dan 67% melakukan perawatan mandiri nonmedis. Terdapat hubungan signifikan antara tingkat pengetahuan dan tindakan pencarian perawatan (p=0,011). Kesimpulan: Remaja dengan pengetahuan baik cenderung memilih tindakan perawatan yang lebih tepat. Edukasi kesehatan reproduksi khususnya dalam perilaku pencarian perawatan yang lebih baik di kalangan remaja putri perlu terus ditingkatkan melalui pendekatan sekolah maupun keluarga.